Memahami dan Menganalisis Struktur Modal dan Kebijakan Dividen dalam Konteks Pendidikan Ekonomi dan Keuangan Perusahaan - Maulida Nikmatul Azizah; Aisyah Brillianta; Moh. Arrijal Ilman Nafi; Cynthia Eka Violita (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to provide a comprehensive understanding of the concepts of capital structure and dividend policy as two essential elements in the teaching of economics and corporate finance. Capital structure refers to a company’s decision in determining the composition of its funding through debt and equity, while dividend policy concerns decisions related to the distribution of profits to shareholders. In the context of economic education, these concepts are not only examined theoretically but also function as important tools to develop students’ analytical abilities in assessing how financial decisions influence corporate performance and firm value. This research employs a literature review method by analyzing twenty academic journals published within the last five years and accessible through Google Scholar. The findings reveal that a solid understanding of capital structure and dividend policy significantly contributes to strengthening students’ financial literacy, particularly in analyzing the relationship between financing decisions, financial risk, dividend stability, and long-term firm sustainability. Furthermore, this study highlights the importance of learning approaches that integrate financial theory with real-world case studies so that students can relate abstract concepts to actual business practices. The implications of this study suggest that educational institutions need to enhance financial analysis–based learning models to produce graduates with strong competencies in understanding the dynamics of corporate financial decision-making in the modern economic landscape.